Tailored Polyurethane Composite Foams for Automotive and Biomedical Applications: Influence of Polyol–Isocyanate Ratios on Density, Texture, and Formation Time - Muhammad Fadhillah Ansyari; Yovi Utami (METAL: Jurnal Sistem Mekanik dan Termal, 2025)
Polyurethane (PU) composite foams have gained significant attention in both the automotive and biomedical industries due to their lightweight structure, tunable mechanical properties, and excellent thermal and acoustic insulation. This study examines how varying the polyol–isocyanate ratio (1:1, 2:3, and 3:2) influences the physical characteristics of PU foams, particularly density, texture, and formation time. Using a batch mixing and molding process, three formulations were synthesized and evaluated. The foam with a 2:3 ratio produced a rigid structure (density: 0.045 g/cm³), suitable for automotive applications such as vibration dampening and structural interior panels. In contrast, the 3:2 ratio resulted in a soft, flexible foam (density: 0.047 g/cm³), which may be applicable in biomedical cushioning, prosthetics, or pressure-relieving supports. The 1:1 ratio generated a semi-rigid foam with the lowest density (0.032 g/cm³), indicating potential use in hybrid comfort–support systems. Formation times ranged from 7.18 to 15 minutes. The results demonstrate that the mechanical and physical properties of PU foams can be customized by adjusting the reactant ratios, enabling their application across multiple sectors. This study provides a foundational understanding of formulation–property relationships for PU composites and supports their integration into energy-efficient vehicles and human-centered biomedical devices.